Understanding the dynamics of labor shares and inflation - Martina Lawless; Karl Whelan (European Central Bank (ECB), 2007)
Calvo-style models of nominal rigidities currently provide the dominant paradigm for understanding the linkages between wage and price dynamics. Recent empirical implementations stress the idea that these models link inflation to the behavior of the labor share of income. Gali, Gertler, and Lopez-Salido (2001) argue that the model explains the combination of declining inflation and labor shares in euro area. In this paper, we show that with realistic parameters, the canonical Calvo-style model cannot explain this outcome. In addition, we show that the model fails very badly in sectoral data. We examine the elements underlying the decline in the labor share in Europe, and conclude that the key factors are related to technological and labor market developments not accounted for in the standard New-Keynesian framework.
Keywords: E31; 330; Labor Share; Phillips curve; Sectoral Data; New-Keynesian Phillips Curve; Theorie; Schätzung; Eurozone